La gestion environnementale des sports de nature : entre laisser-faire, autorité et concertation - Jean-Pierre Mounet (Développement Durable et Territoires)
This article interrogates the consequences of the growth of natural sports in their relationship to the environment. Their recent evolution raises the problem of their durability seen under the angle of the environmental conservation within spaces protected as within the common nature. The controversy concerning their environmental impact seems to exclude the authoritarian solutions. The implemented of a participative democracy is different as it is about spaces protected in strong statutory privileges or not, or about common nature, defining strong or weak mediators. However, the participation remains limited to the spokesmen by leaving aside the very numerous sport followers outside any organization.